Em nome(s) dos interesses: imaginários toponímicos do Rio Grande do Norte na Primeira República - Brito, Anderson Dantas da Silva (2012)
This paper has the imaginary names as a theme, from which we aim to analyze the imaginaries and invested interests that characterized the implementation and the legitimation of the First Republic in Rio Grande do Norte (1889 1930), making the process of registering names history in that place. For the construction of our object, we studied laws and provincial, state and municipal decrees; annual messages of governors; articles of the following newspapers O Povo, A República, Diário do Natal, O Seridoense, A Notícia and Jornal das Moças; the local cartography and historiography that talk about the study of names. The use of these resources, allied to the empiric method, was driven by a theoretic methodological contribution based on the history of the political imaginary, as discussed by Cornelius Castoriadis, René Rémond, Michel de Certeau and Maria Dick. For the understanding of the imaginaries that (de)limited the spaces of Rio Grande do Norte concerning its names during the First Republic, we bring moment back to the two last imperial decades moment of cleavage between Empire and Republic essential for the fomentation of the imaginary that embodied the organization of our study. From this period, we observe, through the names of some cities, how the northern space would be aligned to the imaginary dynamic of the new political system of the nation, and it had followed to a redirection process of the giving names action, according to the interests of the family organization Albuquerque Maranhão, revealed while determining the names of cities, towns, streets, schools, buildings, etc., in thankfulness to the memory of its members. In the sequence we verified how a new dynamic of giving names helped to understand the process of political transition from the Coast to the Sertão, and at the same time affirmed the power of the political and economical seridoense elite towards the government of the state in the two last decades of the First Republic